An extraction method of environmental behaviour characteristics in landscape design. (4th November 2022) - Wang, Shujing; Tang, Haibin
Aiming at the problems of low extraction accuracy and long extraction time in the traditional landscape environmental behaviour feature extraction method, this paper puts forward the environmental behaviour feature extraction method in landscape design. Firstly, the environmental behaviour factors are analysed according to the sense of comfort, security, communication, recognition and achievement, and the environmental behaviour data are obtained. Then, radiometric calibration, atmospheric correction, geometric correction and greyscale processing are carried out for the obtained behaviour data. Then, the scale difference is used to calculate the grey features and detail features of the preprocessed environmental behaviour image, and the grey features and detail features are weighted and fused to extract the environmental behaviour features of landscape architecture. Finally, the simulation results show that the accuracy of the proposed method for landscape environmental behaviour feature extraction is up to 100%, with high extraction accuracy and short extraction time.